A Theoretical Framework for the Accounting and Analytical Maintenance of the Company Business Processes in the Company (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The business processes in the company are defined. An advisability of accounting and analytical maintenance in the context of each individual business processes implementation is given. The goals and objectives of accounting procedures in the context of the maintenance, production and sales of products, goods and delivering the service are outlined. The tasks of analytical work to determine the efficiency of each process are provided.
Keywords: accounting and analytical maintenance, business processes, maintenance process, manufacturing process, sales process.